Explicating Politicians' Arguments for Sex Quotas in Sweden: Increasing Power and Influence Rather Than Increasing Quality and Productivity - Madison, Guy (Frontiers in Communication, 2019)
Quotas are employed or proposed in several European countries, as means to decrease differences in outcomes across groups. The utility and possible side-effects of such measures depend on the underlying model of the relevant variables and their relationships, but this model is not explicit in the political discourse. Here, thematic analysis is applied to infer it from statements that argue for legislated sex quotas in Sweden, issued by leading politicians and government officials. The most common, recurrent propositions are that: (1) Women are at least as able as men; (2) less able men are currently selected over more able women; (3) the proportion of women should be increased to at least 40%, which (4) will increase organisations’ quality and productivity; (5) this should be achieved by means of positive discrimination (e.g. quotas) but (6) not through improved meritocratic assessment. It is shown that these claims are inconsistent, as (a) the less able would be selected only if meritocratic assessment were invalid, but that was not claimed to be the case; (b) positive discrimination will lead to lower rather than higher quality and productivity, as it demands that the less able be appointed if they are female; (c) improved meritocratic assessment was not proposed, although that would more effectively select the more able than would positive discrimination. This suggests a model in which the influence of the favoured group should be increased even if it is presently less able.